THE EFFECT OF HEALTH EDUCATION WITH AUDIO VISUAL MEDIA ON OLDER ADULTS’ KNOWLEDGE ABOUT HYPERTENSION - Siwi Sri Widhowati; Desti Ayu Ningsih; Anik Indriono (Universitas Airlangga, 2022)
Introduction: Along with the increase of older adults’ population in Indonesia, the health problems experienced by the older adults also increase. Hypertension is one of the most common cardiovascular diseases suffered by older adults. Health education is essentially important to increase the awareness of older adults about hypertension. The health education requires media that can be understood and accepted by older adults who may experience physical and cognitive function decline. Method: This study used a pre-experimental method with one group pre-posttest design. A total of 19 older adults met the sample criteria and participated in this study. The instrument used in this research was a questionnaire that has been through expert tests, validity test and reliability tests. Wilcoxon signed rank test was used to determine the significance of the difference between the pretest and posttest scores of the respondents’ knowledge about hypertension. Results: The median of respondents' knowledge before health education was 6 with a range of 0-26. While after being given health education, the median score was 22 with a range of 6-24. There was a significant difference between the pretest and posttest scores. The knowledge of respondents after being given health education seemed to increase, both in terms of gender and age. Conclusion: Health education using audio-visual media can significantly increase the knowledge of the older adults about hypertension in all gender and age categories. Keywords: health education; hypertension; media; older adults